Faktor-Faktor yang Mempengaruhi Pendeteksian Fraud: Pengalaman Audit, Kompetensi dan Skeptisme Profesionalis (Literature Review Audit) - Heru Subekti; Cris Kuntadi (Greenation Publisher & Yayasan Global Resarch National, 2023)
Abstract: This article aims to determine audit experience, competence, and professional skepticism in detecting fraud. This article was carried out by conducting a literature study from various studies that have been done. This article reviews the factors that influence fraud detection: competency, professionalism, and audit experience, a study of audit literature. The results of this literature review article are: 1) audit experience has an effect on fraud detection; 2) dose effect on fraud detection; and 3) professional skepticism has an effect on fraud detection. Abstrak: Artikel ini bertujuan untuk mengetahui pengalaman audit, kompetensi, dan skeptisme profesional dalam mendeteksi fraud. Artikel ini dilakukan dengan melakukan studi literatur dari berbagai penelitian yag sudah dilakukan. Artikel ini mereview faktor-faktor yang mempengaruhi pendeteksian fraud, yaitu: kompetensi, profesionalisme dan pengalaman audit, suatu studi literatur audit. Hasil artikel literature review ini adalah: 1) pengalaman audit berpengaruh terhadap pendeteksian fraud; 2) kompetensi berpengaruh terhadap pendeteksian fraud; dan 3) skeptismie profesional berpengaruh terhadap pendeteksian fraud.